Radial extracorporeal shock wave promotes the treatment of non-union of femoral shaft fractures in children: a case report - Shang, He; Ma, Tao; Liu, Xueqi; Yang, Tianxiang; Luo, Yongzhu; Li, Jun; Liang, Jinpeng; Chen, Desheng (Frontiers in Surgery, 2025)
BackgroundDespite the minimally invasive benefits of flexible intramedullary nails (FIN) for pediatric femoral shaft fractures, nonunion may occur. Traditional surgical revisions carry high trauma and risk, while radial extracorporeal shockwave therapy (rESWT) has potential for promoting bone healing but lacks sufficient evidence in such pediatric cases.MethodsA 4-year-old male with left femoral shaft fracture (AO/OTA 32A2) and FDA-defined nonunion 9 months after FIN fixation received rESWT. Using Gymna ShockMaster 300 (Uniphy), parameters were 6–8 Hz, 2.0–3.0 bar, 1,000–1,500 pulses/week for 3–4 weeks (covering fracture and 2 cm around). Treatment included pre-procedural screening, professional operation, gamified communication, and concurrent rehabilitation.ResultsPost-rESWT, fracture lines blurred then disappeared, with clinical healing achieved and no complications. At 3-month follow-up, intramedullary nail was removed; the patient had 80% weight-bearing capacity, independent walking (mild gait asymmetry), and full weight-bearing recovery later.ConclusionrESWT effectively reverses post-FIN nonunion in pediatric femoral shaft fractures, with advantages of non-invasiveness, safety, and good compliance. It is a feasible alternative for surgery-limited cases, though long-term efficacy needs large-scale validation.